1988
DOI: 10.1152/ajpendo.1988.255.5.e680
|View full text |Cite
|
Sign up to set email alerts
|

Response to deep hypoglycemia does not involve glucoreceptors in carotid perfused tissue

Abstract: In the present study we examined whether the magnified hormonal counter-regulatory response seen during deep hypoglycemia (40 mg/dl) could be attenuated by supplying the forebrain with glucose furnished through carotid infusion. Two protocols were performed in conscious dogs. In the first protocol we infused glucose bilaterally into the carotid circulation to produce a forebrain glycemia of 55 +/- 1 mg/dl (as reflected in the jugular vein), whereas systemic glycemia declined to 39 +/- 2 mg/dl. In the second pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Several studies have reported declining glucagon values during such hyperinsulinemic euglycemic clamps (26,27). This may be particularly important for the dog model in which even a modest infusion of glucose during insulin-induced hypoglycemia has been shown to result in very modest and transient glucagon responses (8,9,11). Despite the general suppression in plasma glucagon over most of the experiment, as arterial glycemia dropped to 2.5 mM glucagon values increased for PER (Table 1).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have reported declining glucagon values during such hyperinsulinemic euglycemic clamps (26,27). This may be particularly important for the dog model in which even a modest infusion of glucose during insulin-induced hypoglycemia has been shown to result in very modest and transient glucagon responses (8,9,11). Despite the general suppression in plasma glucagon over most of the experiment, as arterial glycemia dropped to 2.5 mM glucagon values increased for PER (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…The counterregulatory responses to the brain clamp were then compared with those of a control experiment in which an equivalent level of systemic hypoglycemia was elicited but the brain was also hypoglycemic. After several studies in which CNS glycemia was clamped via either the carotid or vertebral arteries, we were unable to establish any quantitative role for the brain in hypoglycemic detection or counterregulation (8)(9)(10). However, a subsequent study by Biggers et al (11), using similar methodology, reached a different conclusion; i.e., that the brain is essential for full counterregulation.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Despite intensive investigation, the physiological role of these glucose-sensitive regions is highly controversial. Several studies were done to test the role of the brain in directing the counterregulation to insulin-induced hypoglycemia by infusing glucose into the carotid and/or vertebral arteries (1,19,21,22). Cane et al (21) concluded that near-maintenance of brain euglycemia (based on jugular vein glucose) with a bilateral carotid artery glucose infusion was ineffective in alleviating the counterregulatory response to systemic insulin-induced hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neural pathways stimulated by hypoglycemia induce feeding behavior [2]. Hormone responses and symptoms of hypoglycemia tend to be blunted in DM patients treated with insulin, and it is likely that deficient responses to hypoglycemia result from recurrent severe hypoglycemia sustained over many years of insulin replacement [1] CNS mechanisms of autonomic and endocrine responses to hypoglycemia have been studied in dogs and in rodents, and these studies indicate participation of structures in brainstem as well as hypothalamus [3][4][5][6][7][8][9][10][11][12]. Although these animal studies have proven useful in elucidating aspects of neural circuitry underlying counterregulatory hormone secretion, symptom thresholds, per se, cannot be directly assessed in an animal model.…”
Section: Introductionmentioning
confidence: 99%